1999
DOI: 10.1080/026404199365416
|View full text |Cite
|
Sign up to set email alerts
|

The effect of longer-term creatine supplementation on elite swimming performance after an acute creatine loading

Abstract: We investigated the effect of an acute creatine loading (25 g per day for 4 days) and longer-term creatine supplementation (5 g of creatine or 5 g of placebo per day for 2 months) on the performance of 22 elite swimmers during maximal interval sessions. After the acute creatine loading, the mean of the average interval swim times for all swimmers (n = 22) improved (44.3+/-16.5 s before vs. 43.7+/-16.3 s after supplementation; P<0.01). Three of the 22 swimmers did not respond positively to supplementation. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…Improvements in sprint performance after creatine supplementation have been shown in handball [58], football [59], ice hockey [60], soccer [50][51][52]61], swimming [62], and track athletes [63]. Briefly, Kreider in 1998 [22] and Stout in 1999 [59] reported improvements in sprint performance by collegiate American football players after supplementing their diet with combinations of creatine (5.25-15.75 g) and carbohydrates (33-99 g).…”
Section: Sprint Performancementioning
confidence: 99%
“…Improvements in sprint performance after creatine supplementation have been shown in handball [58], football [59], ice hockey [60], soccer [50][51][52]61], swimming [62], and track athletes [63]. Briefly, Kreider in 1998 [22] and Stout in 1999 [59] reported improvements in sprint performance by collegiate American football players after supplementing their diet with combinations of creatine (5.25-15.75 g) and carbohydrates (33-99 g).…”
Section: Sprint Performancementioning
confidence: 99%
“…The most likely benefits for swimmers come from using creatine in the training phase to enhance training adaptations to interval and resistance training. However, while there are studies that report an enhancement of the performance of such sessions in highly trained swimmers 71 , there is some controversy about it at the moment 72 .…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesized that CRE would improve sprint performance, as CRE is thought to be particularly effective for repetitive high-intensity bouts lasting ≤30 seconds (5). A number of previous studies have shown CRE supplementation to improve performance on both single (34) and repeated (4, 9, 30, 34, 36) sprint tests, with samples ranging from recreationally active (30) to elite-level athletes (36). However, McKenna et al (26) demonstrated that CRE did not improve performance on a repeated sprint test consisting of five ten-second sprints with variable rest periods in recreationally active subjects.…”
Section: Discussionmentioning
confidence: 99%